ETHICAL CONSUMPTION FOR THE PROMOTION OF HUMAN DIGNITY IN A GLOBALIZED WORLD - Bertoncini, Mateus; Lins, Elaine Braga Martins Ribeiro; Lins, Elaine Braga Martins Ribeiro (Revista de Direito Brasileira, 2019)
This article is a study on consumer ethics. Its purpose is to foster consumption practices that contribute to the reduction of violations of the human dignity, as well as to contribute to the maintenance of an ecologically balanced environment. It starts with a study on general notions of ethics. Then, it moves on to an approach on the human dignity. Aspects related to the consumer society and environmental sustainability are elicited. It presents as a key problem the issue of the modern society's overconsumption, in a global perspective, fed by economic and selfish interests that generate serious environmental and social consequences, which need to be researched, understood and equated not only scientifically but also in the perspective of ethics, in the construction of the so-called ethical consumption, in a way that promotes the sustainability of the planet and the human dignity, as a necessary response to said anti-ethical or unethical consumption, which is absolutely unsustainable. Finally, topics related to impacts on Economy and social responsibility are addressed. Deductive and critical method were employed, grounded in bibliographical research.